Data Hiding Technique for Color Images using Pixel Value Differencing and Chaotic Map - Nisreen Yassin (Jordanian Journal of Computers and Information Technology, 2022)
The huge advance in information technology and communication resulted in extreme usage of digital networks that makes information security playing an important role as never before. Steganography is the art of hiding secret message bits into different multimedia data using either spatial domain or frequency domain to provide security for the transferred information against unauthorized access. Most of the techniques that apply Pixel Value Differencing approach (PVD) depend on sequential embedding manner, which lacks security. In the proposed method, a complex chaotic map is used to randomly choose the coefficients pairs for embedding the secret message. First, the cover image is transformed using IWT. Then, the embedding process starts in the highest frequency band of IWT and continues to the next sub-bands. Adaptive embedding is performed according to intensity variation between pixel pairs using PVD and Least Significant Bit substitution (LSB). Non-sequential embedding performed by using chaotic map lets the method more secure. The experimental results show that the proposed technique achieves high PSNR with improved capacity compared to other techniques. [JJCIT 2022; 8(3.000): 242-255]